Influence of stage of maturity/cutting on the iodine status of maize (Zea mays), oat (Avena sativa) and berseem (Trifolium alexandrium) - Bedi, S P S (The Indian Journal of Animal Sciences, 2012)
Samples of cultivated fodder, viz. maize, oat and berseem were collected from fields (10 in each case) of varing land sizes in term of hectares, selected at random at the Institute's agriculture from, at preflowering, flowering and maturity stages (maize and oat) and at first to fifth cut (berseem from December to April). The samples after processing were analysed for iodine status and average iodine contents were 0.4616 ± 0.0529, 0.4426 ± 0.0123, 0.4478 ± 0.209 and 0.276 ± 0.077, 0.179 ± 0.042, 0.192 ± 0.091µg/g of DMB at different stages of maturity in maize and oat fodder respectively and 0.196 ± 0.081, 0.159 ± 0.078, 0.351 ± 0.158, 0.368 ± 0.106 and 0.303 ± 0.093 µg/g DMB in first to fifth cut of berseem fodder, respectively. The study revealed large variations in the values of iodine in each fodder at particular stage and between the different stages of maturity and cutting.